Internal and external co-engineering of stable cathode interface improves cycle performance of polymer sodium batteries - Pan, Jun (2023)
The development of polymer sodium batteries requires cathode materials with stable interfaces to avoid poor interfacial contact and interfacial side reactions during cycling. Here, a co-engineering strategy is deployed to tailor the cathode internal structure and improve the cathode interface stability through bonding interactions. Internally, the effect of low-cost Fe substitution in the obtained Na0.67Mn2/3Fe1/3O2 cathode material renders favorable effects in several aspects. First, the increased lattice constant facilitates Na+ intercalation and thereby lowers the diffusion barrier of Na+ ions. Second, it increases the electronic conductivity, thereby improving the reaction reversibility. Third, the Mn O bond length is shortened, which alleviates the Jahn-Taylor effect and improves structural stability. In addition to these internal effects, the Fe O B bond interactions due to Fe substitution promote the decomposition of the tris(trimethylsilane)borate additive and the formation of a dense and uniform cathode electrolyte interface film, leading to improved cycling stability. Owing to the co-engineering of both internal structure and surface modification, the polymer solid-state sodium battery with a stable interface exhibits a specific capacity of 85.2 mAh g-1 after 800 cycles at 1 C.